Advancements in Electrochemical Sensing Technology for Heavy Metal Ions Detection - Yu Tian; Jinli Liu; Jiali Qiao; Fuguo Ge; Yukun Yang; Qi Zhang (Food Chemistry: X)
Most heavy metal ions are carcinogenic and non-biodegradable, posing threats to ecological balance and human health in trace amount. Therefore, there is a pressing demand for rapid and dependable detection technologies. Electrochemical sensing technology distinguishes itself with its ease of use and swiftness, rendering it perfect for the expeditious detection of heavy metal elements. This review examines various electrochemical detection techniques for on-site real-time monitoring of heavy metal ions. Advanced methods using innovative electrochemical sensor technologies are explored, highlighting the importance of sensing strategies for the quick and easy monitoring of metal levels in different environments. Additionally, the role of nanotechnology and electrochemical techniques in enhancing the sensitivity and selectivity of sensors for better detection of heavy metals is discussed. Finally, the future direction of sensor development is addressed, focusing on integrating new materials and technologies to improve the performance of sensor in environmental monitoring, food safety and public health.